2014
DOI: 10.1099/vir.0.058867-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of virions is strictly required for turnip yellows virus long-distance movement in plants

Abstract: Viral genomic RNA of the Turnip yellows virus (TuYV; genus Polerovirus; family Luteoviridae) is protected in virions formed by the major capsid protein (CP) and the minor component, the readthrough (RT*) protein. Long-distance transport, used commonly by viruses to systemically infect host plants, occurs in phloem sieve elements and two viral forms of transport have been described: virions and ribonucleoprotein (RNP) complexes. With regard to poleroviruses, virions have always been presumed to be the long-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The finding that P17 associates with the PLRV virion protein interaction network is highly consistent with evidence that shows poleroviruses traffic systemically as virions [47] and that, in N. benthamiana, P17 aids in the efficient, systemic movement of PLRV [48]. A total of 1107 plant proteins were classified as category I proteins.…”
Section: Category I Protein Interactionssupporting
confidence: 84%
“…The finding that P17 associates with the PLRV virion protein interaction network is highly consistent with evidence that shows poleroviruses traffic systemically as virions [47] and that, in N. benthamiana, P17 aids in the efficient, systemic movement of PLRV [48]. A total of 1107 plant proteins were classified as category I proteins.…”
Section: Category I Protein Interactionssupporting
confidence: 84%
“…) was gained by analysing pumpkin phloem sap (Xoconostle‐Cazares et al ., ; Yoo et al ., ). It is well established that viral RNAs in the phloem are always found in ribonucleoprotein complexes (RNPs) with virally produced proteins (Hipper et al ., ). In addition, host factors can assist virus phloem transport.…”
Section: Phloem As a Conduit For Macromoleculesmentioning
confidence: 97%
“…In plants, polerovirus infection is limited to phloem tissues: cell-to-cell movement occurs between vascular parenchyma cells, companion cells and the enucleated sieve elements whereas long-distance movement follows the sieve elements. Because polerovirus particles were detected in plasmodesmata connecting phloem cells [3][5], the virus is thought to move in the form of virions and recent data confirmed that particles of Turnip yellows virus (TuYV, Polerovirus genus) are essential for long-distance movement [6]. Polerovirus have isometric particles of about 25 nm of diameter containing two structural proteins: the major coat protein (CP) encoded by ORF3 and a minor component, referred to as the readthrough (RT) protein, which is synthesized after ribosomes bypass the ORF3 stop codon during translation.…”
Section: Introductionmentioning
confidence: 96%